Management characteristics and prognosis after stroke in China: findings from a large nationwide stroke registry. Issue 1 (22nd June 2020) - Qin, Haiqiang; Chen, Yiping; Liu, Gaifen; Turnbull, Iain; Zhang, Runhua; Li, Zixiao; Wang, Yilong; Liu, Liping; Zhao, Xingquan; Chen, Zhengming; Wang, Yongjun
Abstract : Background and purpose: There is limited nationwide evidence about the standard management characteristics of stroke types and prognosis in China. This study aimed to assess clinical characteristics, in-hospital and after-discharge management characteristics and prognosis for stroke types in China. Methods: A nationwide registry recruited 14 244 imaging-confirmed first-ever incident strokes from 132 hospitals across 31 provinces of China during 2007–2008, recording presenting characteristics, diagnostic procedures and in-hospital treatment. After hospital discharge, patients were followed up for 6 months. Conventional statistical methods were used to examine the patterns of management and prognosis. Results: Overall, 68.7%, 26.9% and 4.4% were ischaemic stroke (IS), intracerebral haemorrhage (ICH), and subarachnoid haemorrhage (SAH), respectively. Only 20% were managed in a dedicated stroke unit. Among IS, 1.3% received thrombolysis within 3 hours after symptom onset, whereas the proportions of receiving in-hospital antiplatelet therapy, neuroprotective agents and traditional Chinese medicines (TCM) were 88.4%, 69.7% and 70.6%, respectively. For ICH, 63.3% and 36.3% received neuroprotective agents and TCM in hospital, respectively. At discharge, 70.7% and 38.0% of the patients with IS were given antiplatelet and statin therapies, respectively, decreasing to 64.8% and 23.9%, respectively, at 6 months. In-hospital mortality was 3.2%, 9.3% and 10.1% for IS, ICH and SAH, respectively, with a further 8.6%, 18.2% and 22.0%, respectively, died by 6 month. Meanwhile, in-hospital recurrence rate was 2.6%, 1.9% and 7.2% for IS, ICH and SAH, respectively, with a further 8.0%, 5.1% and 7.5%, respectively, recurred by 6 month. Conclusions: In China, the mortality rate of stroke is lower than that reported from west populations, though most strokes are not managed in specialised stroke unit. There is widespread use of some unproven therapies but limited proven treatments, especially after discharge, leading to unnecessary recurrent risks.